Antiangiogenic effect of somatostatin receptor subtype 2 on pancreatic cancer cell line: Inhibition of vascular endothelial growth factor and matrix metalloproteinase-2 expression in vitro - Kumar, Manoj (World J Gastroenterol, 2004)
AIM: To investigate the anti-angiogenic effect of somatostatin receptor subtype 2 (SSTR2) gene transfer into pancreatic cancer cell line PC-3, and the mechanisms involved in this effect. METHODS: The full length human SSTR2 cDNA was introduced into pancreatic cancer cell line PC-3 by lipofectamine-mediated transfection. Positive clones were screened by G418 and stable expression of SSTR2 was detected by immunohistochemistry SABC methods and RT-PCR. Enzyme-linked immunosorbent assay (ELISA) was used to detect vascular endothelial growth factor (VEGF) levels in the cell culture supernatants of SSTR2-expressing cells, vector control and mock control cells. Furthermore, the expressions of VEGF and matrix metalloproteinase-2 (MMP-2) were detected by immunohistochemistry SABC methods and RT-PCR in these cells. RESULTS: VEGF levels in the cell culture supernatants were significantly reduced in the SSTR2-expressing cells (first week, 172.63 ± 21.2 ng/L and after two months, 198.85 ± 26.44 ng/L) compared with the vector control (first week, 790.39 ± 86.52 ng/L and after two months, 795.69 ± 72.35 ng/L) and mock control (first week, 786.42 ± 90.62 ng/L and after two months, 805.32 ± 84.36 ng/L) (P < 0.05). The immunohistochemical assay showed a significant reduction of the integral optical density of VEGF and MMP-2 in the SSTR2-expressing cells (42.25 ± 8.6 and 70.5 ± 6.25, respectively) compared with the vector control (85.75 ± 12.9 and 110.52 ± 13.5, respectively) and mock control (82.6 ± 9.28 and 113.56 ± 9.62, respectively) (P < 0.05). Conversely, the average gray value of VEGF and MMP-2 was significantly increased in the SSTR2-expressing cells (121.56 ± 8.43 and 134.46 ± 19.95, respectively) compared with the vector control (55.72 ± 5.6 and 62.26 ± 12.68, respectively) and mock control cells (58.48 ± 6.2 and 65.49 ± 9.16, respectively) (P < 0.05). Moreover, the expressions of VEGF mRNA and MMP-2 mRNA were significantly reduced in the SSTR2-expressing cells (0.1384 ± 0.017 and 0.2343 ± 0.070, respectively) compared with the vector control (1.024 ± 0.117 and 0.806 ± 0.119, respectively) and mock control (1.085 ± 0.105 and 0.714 ± 0.079, respectively) (P < 0.05). CONCLUSION: The expression of reintroduced human SSTR2 gene exerts its antiangiogenic effects by down-regulating the expressions of the factors involved in tumor angiogenesis and metastasis, suggesting SSTR2 gene transfer as a new strategy of gene therapy for pancreatic cancer.